Інтеркультурна модель як інноваційний чинник розвитку міжкультурної інтеграції міста - Афанасьєва, Людмила Василівна; Афанасьева, Людмила Васильевна; Afanasieva, Liudmyla V.; Кузнєцова, Альона Сергіївна; Кузнецова, Алена Сергеевна; Kuznietsova, Alona S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті йдеться про те, що Рада Європи разом із групою пілотних міст запустила амбітну ініціативу щодо розвитку підходу до інтеграції різних спільнот, що стосується дефіциту згуртованості, та пропонує новий шлях – програму «Інтеркультурні міста». У ході дослідження виявлено, що міста можуть отримати величезну користь із різноманітних навичок, підприємництва й креативності, пов’язаних із розмаїттям, тим самим полегшуючи міжкультурну взаємодію та співтворчість. Особливу увагу приділено розробці інтеркультурної моделі полікультурного міста як успішного чинника міжкультурної інтеграції його соціокультурного простору. One of the most important human need – a need for belonging and identity of the community, regardless of language, origin, religion and other differences. In practice, this means recognizing the importance of different cultures and their right to participate in the creation of a common identity, which is defined by diversity, pluralism and respect for human rights and fundamental freedoms. In the article, the authors draw attention to the fact that to be successful, intercultural integration model must operate at a strategic level. Currently, more than 60 cities all over Europe used this model (members of the European and national networks), including Ukraine, as well as Mexico City, Montreal, city of Japan and South Korea. The model considers the integration is not as dealing with the needs of people who need help to act accordingly, but as a process in which social and economic institutions able to determine and increase the use of the skills and talents of all and give everyone the opportunity to become productive members of society.
Intercultural Model as an Innovative Factor in the Development of Intercultural Integration of the City
Keywords: поліетнічне місто; інтеркультурне місто; індекс інтеркультурності; соціокультурний прострір міста; multi-ethnic city; Intercultural city; the index intercultural; socio-cultural space of the city